Eficiencia de diferentes criterios de selecao em populacoes segregantes de mandioca - Bueno, A. (International Center for Tropical Agriculture, 1991)
The efficiency of different selection criteria (root wt., aerial part wt., total wt., no. of roots/plant, HI) applied to segregating populations of cassava crosses was assessed in expt. carried out at the Centro Nacional de Pesquisa de Mandioca e Fruticultura in Cruz das Almas (Bahia, Brazil). Samples of seedlings from 5 open-pollinated families were used. Clones resulting from the selection were assessed in single rows arranged in a random block design, where treatments were the selection criteria and the replicates the no. of clones selected in each sample. The expt. was repeated in 1985/86 in bordered plots. Mean values and variances were similar. The selection criteria were therefore applied impartially to the samples. Some differences were found in the assessments of lines and plots. Total wt. proved to be the most efficient selection criterion; regarding plots, HI and no. of roots/plant were the most efficient. Root wt. proved to be inefficient as a selection criterion in segregating populations. The most efficient criteria were total wt., no. of roots/plant, and HI, applied together. (AS-CIAT)